Trainability of young athletes and overtraining - Matos, N.; Winsley, R. J. (Journal of Sports Science & Medicine, 2007)
Exercise adaptations to strength, anaerobic and aerobic training have been extensively studied in adults, however, young people appear to respond differently to such exercise stimulus in comparison to adults. In addition, because overtraining in young athletes has received little attention, this important area is also discussed. Resistance training in children can be safe and effective. It has the potential to improve sport performance, enhance body composition and reduce the rate of sport incurred injury. Furthermore, with the appropriate stimulus, prepubertal and adolescent athletes can show significant increments in muscle strength (13 - 30%). Children can improve anaerobic power (3%-10% Mean Power and 4%-20% in Peak Power), although the mechanisms responsible for the improvements in children remain unclear. Children show a 'reduced' trainability of peak VO2 in comparison to adults. Nevertheless, their aerobic power is trainable, with improvements reported at approximately 5%. Moreover, improvements in other variables like exercise economy or lactate threshold may occur without significant changes in peak VO2 The limited evidence available indicates that overtraining is occurring in young athletes (30% prevalence), highlighting the importance of further research in to all the possible contributing factors - physiological, psychological and emotional - when investigating overtraining.